Characterization of Alkali-Induced Quartz Dissolution Rates and Morphologies - Ali, A.M. (Springer Verlag, 2017)
A number of studies have investigated the impact of alkali cations on quartz dissolution to increase the understanding of natural rock weathering and enhance the predictability of silica behaviour in reservoir systems. However, there are few evidences for how alkali cations approach the quartz surface. Thus, this study is an attempt to provide empirical evidence on the interaction of electrolytes (Na +, K +, Ca 2 +) with quartz surface. Bulk quartz grains and clean-faced single quartz crystals were dissolved/etched in varying pH solutions of acidic, near-neutral/neutral and alkali solutions (KOH, NaOH, KCl, NaCl, CaCl 2, CH 3COOH , HCl). The amount of dissolved silica was measured with molybdate spectrophotometry method, while variations in quartz surface morphology were studied using scanning electron microscopy attached with EDX. Quartz dissolution rates varied with pH, hydrated radius and hydrolysis constants of alkali cations in the order: Ca 2 +< Na +< K +. Relatively deeper triangular etch pits were observed in quartz dissolved in KOH and NaOH solutions, while shallower pits formed in neutral solutions, and exsolution faces and lamellae were formed in quartz dissolved in low-pH solutions. The results also showed that interfacial secondary phases of cationic silicates play a key role in quartz dissolution. © 2017, King Fahd University of Petroleum & Minerals.